Perancangan Sekolah Luar Biasa C dan E di Kota Surakarta dengan Pendekatan Arsitektur Perilaku - Awangsih, Annisa Faradilla; Endangsih, Tri; Kurniasih, Sri (MAESTRO, 2021)
The special education school C and E is a formal school education facility specifically for mentally disabled and unsociable children who require special attention in education and character control with an adapted curriculum. With the application of behavioral architecture, it is expected to create educational facilities that could adapt to behavior of the children with special needs. Ki Hajar Dewantara street, Surakarta City, Central Java was chosen to be the location of the site used in design. Considering that the area is an educational area, it makes the surrounding environment very conducive for the school activity.